2014
DOI: 10.1002/anie.201309508
|View full text |Cite
|
Sign up to set email alerts
|

Nature’s Chemical Signatures in Human Olfaction: A Foodborne Perspective for Future Biotechnology

Abstract: The biocatalytic production of flavor naturals that determine chemosensory percepts of foods and beverages is an ever challenging target for academic and industrial research. Advances in chemical trace analysis and post-genomic progress at the chemistry-biology interface revealed odor qualities of nature's chemosensory entities to be defined by odorant-induced olfactory receptor activity patterns. Beyond traditional views, this review and meta-analysis now shows characteristic ratios of only about 3 to 40 genu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
550
1
17

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 447 publications
(576 citation statements)
references
References 243 publications
8
550
1
17
Order By: Relevance
“…[5] Especially important to this concept are odorants that impart a distinct effect as a result of being present at suprathreshold concentrations (defined in terms of odour activity value, OAV ¼ concentration/aroma detection threshold, with OAV . 1) and compounds having characteristic aroma qualities that may define a particular varietal wine.…”
Section: Varietal Wine Aromasmentioning
confidence: 99%
“…[5] Especially important to this concept are odorants that impart a distinct effect as a result of being present at suprathreshold concentrations (defined in terms of odour activity value, OAV ¼ concentration/aroma detection threshold, with OAV . 1) and compounds having characteristic aroma qualities that may define a particular varietal wine.…”
Section: Varietal Wine Aromasmentioning
confidence: 99%
“…Therefore, it is no surprise that, although aided by visual inspection, the final recognition and quality evaluation of food crops made by consumers are mainly mediated by its flavor perception. Human flavor perception is induced by the interaction of volatile odor-active and non-volatile taste-active molecules with ~390 odorant receptor proteins located in the regio olfactoria in the nose and ~40 taste receptor proteins on the tongue [75]. To meet the consumers' demand on continuous available, fresh foods with a premium quality, the "flavor blueprint" of a golden standard, which is a combinatorial code of the entire set of odor-and taste-active metabolites in their natural concentrations, has to be known [76].…”
Section: Sensomics -A Phenotyping Tool To Characterize Crops Flavor Imentioning
confidence: 99%
“…This so called molecular sensory science or sensomics approach has especially been shaped by Peter Schieberle´s and Thomas Hofmann´s working groups during the last three decades [75,76]. Today, it is well accepted that the presence of certain structural elements, so-called olfactophores and gustophores, as well as specific concentrations exceeding the sensory thresholds are important prerequisites of low molecular weight metabolites to become flavor-active [76].…”
Section: Sensomics -A Phenotyping Tool To Characterize Crops Flavor Imentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, short-chained carboxylic acids are typically described as smelling "sweaty" or reminiscent of "body odor" (Dravnieks, 1985). It is well-established that the odor quality of both bodily secretions and of food is often characterized by so-called "key compounds" (sometimes also referred to as "character impact compounds") (Dunkel et al, 2014). Animal studies have shown that certain "key compounds" of complex predator odors, for example, are sufficient to elicit adaptive behavioral responses in prey species (Apfelbach et al, 2005) and thus clearly demonstrate their behavioral relevance.…”
Section: Within-species Comparison With Other Classes Of Aliphatic Odmentioning
confidence: 99%